2003
DOI: 10.1348/014466503322528928
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of food‐related problems in individuals with Prader‐Willi syndrome

Abstract: The development of a twenty item questionnaire, the Food Related Problem Questionnaire (FRPQ), with four subscales (preoccupation with food, impairment of satiety, difficulty with self-control and other food-related 'challenging' behaviour of food-related problems) for use with individuals with Prader-Willi syndrome (PWS) is described.. Test-retest and inter-rater reliability for the total score are .78 and .86 respectively. Subscale test-retest and inter-rater reliability are acceptable for three subscales (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 43 publications
1
49
1
Order By: Relevance
“…Thus, our results are not totally consistent with the previous studies. On the other hand, Russell and Oliver [19] showed a within-syndrome variability of eating behavior measurements in PWS, and the large variability in the small number participating in the present study might be one of the explanations for the discrepancies. A previous study of eating behavior monitored with the VIKTOR equipment showed that 50% of children with PWS had accelerating eating curves [4] , but this pattern could not be confirmed in our adult group.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, our results are not totally consistent with the previous studies. On the other hand, Russell and Oliver [19] showed a within-syndrome variability of eating behavior measurements in PWS, and the large variability in the small number participating in the present study might be one of the explanations for the discrepancies. A previous study of eating behavior monitored with the VIKTOR equipment showed that 50% of children with PWS had accelerating eating curves [4] , but this pattern could not be confirmed in our adult group.…”
Section: Discussioncontrasting
confidence: 55%
“…Structured psychiatric interviews, such as the K-SADS-PL (Kaufman et al, 1997) and NIMH-DISC-IV (Shaffer, Fisher, Lucas, Dulcan, & Schwab-Stone, 2000), represent another option for measuring psychiatric outcome, but the application of these methods to an IDD population in a clinical trial remain relatively unknown. In need of further exploration and development are outcome measures to assess frontal systems, motivation/initiation (Malloy & Grace, 2005), eating/appetite regulation (Russell & Oliver, 2003), self-talk/voices (Chadwick, Lees, & Birchwood, 2000), regression/functional decline, and specific psychopathologies such as psychosis (Hatton et al, 2005). …”
Section: Resultsmentioning
confidence: 99%
“…Russell and Oliver (2003) Roof et al, 2000), very few studies have used such reports due to issues with reliability and validity (Dykens et al, 2007).…”
Section: Assessment Of Internal States Within Individuals With Intellmentioning
confidence: 99%